The Impact of On-Target Resistance Mediated by EGFR-T790M or EGFR-C797S on EGFR Exon 20 Insertion Mutation Active Tyrosine Kinase Inhibitors - Ikei S. Kobayashi, MD, PhD; William Shaffer, MS; Hollis Viray, MD; Deepa Rangachari, MD; Paul A. VanderLaan, MD, PhD; Susumu S. Kobayashi, MD, PhD; Daniel B. Costa, MD, PhD (JTO Clinical and Research Reports, 2024)
Introduction: Mechanisms of resistance to EGFR exon 20 insertion mutation active inhibitors have not been extensively studied in either robust preclinical models or patient-derived rebiopsy specimens. We sought to characterize on-target resistance mutations identified in EGFR exon 20 insertion-mutated lung cancers treated with mobocertinib or poziotinib and evaluate whether these mutations would or would not have cross-resistance to next-generation inhibitors zipalertinib, furmonertinib, and sunvozertinib. Methods: We identified mechanisms of resistance to EGFR exon 20 insertion mutation active inhibitors and then used preclinical models of EGFR exon 20 insertion mutations (A767_V769dupASV, D770_N771insSVD, V773_C774insH) plus common EGFR mutants to probe inhibitors in the absence/presence of EGFR-T790M or EGFR-C797S. Results: Mobocertinib had a favorable therapeutic window in relation to EGFR wild type for EGFR exon 20 insertion mutants, but the addition of EGFR-T790M or EGFR-C797S negated the observed window. Zipalertinib had a favorable therapeutic window for cells driven by EGFR-A767_V769dupASV or EGFR-D770_N771insSVD in the presence or absence of EGFR-T790M. Furmonertinib and sunvozertinib had the most favorable therapeutic windows in the presence or absence of EGFR-T790M in all cells tested. EGFR-C797S in cis to all EGFR mutations evaluated generated dependent cells that were resistant to the covalent EGFR tyrosine kinase inhibitors mobocertinib, zipalertinib, furmonertinib, sunvozertinib, poziotinib, and osimertinib. Conclusions: This report highlights that poziotinib and mobocertinib are susceptible to on-target resistance mediated by EGFR-T790M or -C797S in the background of the most prevalent EGFR exon 20 insertion mutations. Furmonertinib, sunvozertinib, and to a less extent zipalertinib can overcome EGFR-T790M compound mutants, whereas EGFR-C797S leads to covalent inhibitor cross-resistance—robust data that support the limitations of mobocertinib and should further spawn the development of next-generation covalent and reversible EGFR exon 20 insertion mutation active inhibitors with favorable therapeutic windows that are less vulnerable to on-target resistance.